2018
DOI: 10.3390/jcm7120533
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients At-Risk of QT Interval Prolongation during Medication Reviews: A Missed Opportunity?

Abstract: The prolongation of the QT interval is a relatively rare but serious adverse drug reaction. It can lead to torsade de pointes, which is potentially life-threatening. The study’s objectives were: determine the use of QT interval-prolonging drugs in an elderly community-dwelling population at risk of medication misadventure and identify recommendations regarding the risk of QT interval prolongation made by pharmacists when performing medication reviews. In a retrospective evaluation, 500 medication review report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 13 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…The categories of intervention recommendations (monitoring serum electrolytes and ECG, or stopping or reducing the dosage of the drug) were similar to those of another study investigating drug-induced QT prolongation. 38 Therefore, this paper suggests that pharmacists perform a thorough medication review and recommends monitoring ECG in patients using drugs with known risk of QT interval prolongation taking additional risk factors such as advanced age, gender, and electrolyte derangements into consideration in elderly population. 38 Potentially inappropriate prescribing is highly prevalent among geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The categories of intervention recommendations (monitoring serum electrolytes and ECG, or stopping or reducing the dosage of the drug) were similar to those of another study investigating drug-induced QT prolongation. 38 Therefore, this paper suggests that pharmacists perform a thorough medication review and recommends monitoring ECG in patients using drugs with known risk of QT interval prolongation taking additional risk factors such as advanced age, gender, and electrolyte derangements into consideration in elderly population. 38 Potentially inappropriate prescribing is highly prevalent among geriatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…38 Therefore, this paper suggests that pharmacists perform a thorough medication review and recommends monitoring ECG in patients using drugs with known risk of QT interval prolongation taking additional risk factors such as advanced age, gender, and electrolyte derangements into consideration in elderly population. 38 Potentially inappropriate prescribing is highly prevalent among geriatric patients. 3 Di Giorgio et al 39 that 49% and 27% of the geriatric patients had at least one PIM during hospitalization period according to Beers and STOPP criteria, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A scientific review board, based on ongoing and systematic analysis of evidence, categorised drugs into three categories based on their ability to cause QT prolongation or TdP [14]. These categories are (1) known risk of TdP—drugs that prolong the QT interval and are clearly associated with a known risk of TdP, even when taken as recommended; (2) possible risk of TdP—drugs that can cause QT prolongation but currently lack evidence for a risk of TdP when taken as recommended; and (3) conditional risk of TdP—drugs that are associated with TdP but only under certain conditions or by creating conditions that facilitate or induce TdP [14]. The website also has a fourth category, drugs that should be avoided in individuals with congenital long QT syndrome; however, this category was not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…An earlier publication from our research group [14] addressed the identification of community-dwelling patients at risk of QT interval prolongation during medication reviews, and concluded that there is a need to improve knowledge and awareness of this topic amongst pharmacists performing such medication reviews. This complementary research explored the role of pharmacists in reducing the risk of QT prolongation in residential aged care patients by conducting medication reviews.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the medical specialties focusing on LQTS, drug‐induced QT prolongation is relevant to a much wider group of health care professionals involved in therapeutic decisions, for example, physicians in family practice and a wide variety of medical specialties, physician assistants, nurses, and pharmacists and hence this article's focus on this topic. A wide range of drugs and drug classes for many conditions as diverse as liver and kidney disease, chronic obstructive pulmonary disease, psychiatric conditions, and posttraumatic stress disorder have an identified proarrhythmic liability.…”
Section: Normal Cardiac Ion Channel Activity Inherited Long Qt Syndrmentioning
confidence: 99%